Sexplanation! - Irene Stevens (Scottish Journal of Residential Child Care)
Just in time to coincide with new initiatives around personal, social and health education The National Youth Agency has relaunched its classic youth work resource, the Grapevine Game. Given a 21st century makeover and re-titled Sexplanation! it retains its board game format which has been shown to open up honest, frank and informative discussions around sex and relationships.